Improving economic evaluations in stroke: A report from the ESO Health Economics Working Group. (June 2020) - Cadilhac, Dominique A; Kim, Joosup; Wilson, Alastair; Berge, Eivind; Patel, Anita; Ali, Myzoon; Saver, Jeffrey; Christensen, Hanne; Cuche, Matthieu; Crews, Sean; Wu, Olivia; Provoyeur, Marine; et al.
Introduction: Approaches to economic evaluations of stroke therapies are varied and inconsistently described. An objective of the European Stroke Organisation (ESO) Health Economics Working Group is to standardise and improve the economic evaluations of interventions for stroke. Methods: The ESO Health Economics Working Group and additional experts were contacted to develop a protocol and a guidance document for data collection for economic evaluations of stroke therapies. A modified Delphi approach, including a survey and consensus processes, was used to agree on content. We also asked the participants about resources that could be shared to improve economic evaluations of interventions for stroke. Results: Of 28 experts invited, 16 (57%) completed the initial survey, with representation from universities, government, and industry. More than half of the survey respondents endorsed 13 specific items to include in a standard resource use questionnaire. Preferred functional/quality of life outcome measures to use for economic evaluations were the modified Rankin Scale (14 respondents, 88%) and the EQ-5D instrument (11 respondents, 69%). Of the 12 respondents who had access to data used in economic evaluations, 10 (83%) indicated a willingness to share data. A protocol template and a guidance document for data collection were developed and are presented in this article. Conclusion: The protocol template and guidance document for data collection will support a more standardised and transparent approach for economic evaluations of stroke care.